Diseñar el sistema de gestión documental de la compañía Impresos Panzzer SAS. (2017)
The main objective of this monograph was to design a document management system for the human resources, accounting and billing departments of the company Impresos Panzzer SAS, based on the guidelines of the general law of files 594 of 2000, in addition to the ISO standard 15489-1 of 2006. To achieve the design approach, information obtained from the company was collected in each of the departments in question in order to establish the current status of the documentary classification.